1960
DOI: 10.1113/jphysiol.1960.sp006376
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electrical stimulation of viseral afferent nerve fibres on monosynaptic and polysynaptic reflex responses

Abstract: The first investigation of the nature and time course of viscero-somatic interaction was made by Downman (1955) in anaesthetized, decerebrate and spinal cats. Later, Evans & McPherson (1958) showed that electrical stimulation of the afferent fibres in the sympathetic chain or splanchnic nerves facilitated monosynaptic reflexes and inhibited long-latency polysynaptic reflexes elicited from the hind-limb nerves of chloralosed and spinal cats. The present paper describes additional features of these interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1966
1966
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Further, they showed that this effect on the knee-jerk was not related to the cardiovascular effect of vagal stimulation. Evans & McPherson (1960) were, however, unable to confirm these results. These latter workers stimulated the cervical vagus with as much as 70 V but obtained equivocal results on the monosynaptic reflex.…”
Section: Methodscontrasting
confidence: 38%
“…Further, they showed that this effect on the knee-jerk was not related to the cardiovascular effect of vagal stimulation. Evans & McPherson (1960) were, however, unable to confirm these results. These latter workers stimulated the cervical vagus with as much as 70 V but obtained equivocal results on the monosynaptic reflex.…”
Section: Methodscontrasting
confidence: 38%
“…The only differences from the methods employed in previous papers (Evans & McPherson, 1958, 1960and McPherson, 1966a were (a) the method of myograph recording and (b) the level of transection of the spinal cord. In the present series of experiments muscle contractions were recorded using a rectilinear potentiometer fed through a d.c. amplifier to a potentiometric recorder.…”
Section: Methodsmentioning
confidence: 96%
“…It is also possible that these inhibitory pathways are themselves inhibited when voluntary restraint is removed. In addition to these primary reflex mechanisms there may be other associated reflexes of minor importance in the regulation of micturition (see Garry et al 1959;Evans & McPherson, 1960). Thus, there is a progressive and self-reinforcing cycle which increases and maintains the contraction of the vesical musculature during the act of voiding.…”
Section: Discussionmentioning
confidence: 99%